The Role Sharia Fintech Support Sustanaible Development Goals Program (SDGs) - Trimulato Trimulato; M. Cholil Nafis; Euis Amalia (ITB AAS INDONESIA Surakarta, 2022)
Abstract Islamic finance products are increasingly varied, including the presence of shariah fintech. The development of sharia fintech has a role in supporting the Sustainable Development Goals (SDGs. This study aims to determine the development of sharia fintech, and to determine the role sharia fintech in supporting the SDGs program. This type of research is literature study with the nature of the research is qualitative. This study uses descriptive qualitative data analysis techniques. The results of this study indicate the development sharia fintech assets in December 2020 amounting to 74,677,072,107, growing to reach 47.53 percent, with the number of sharia fintech lending actors 10. Types of sharia fintech are peer to peer landing (P2P), payment instruments, and crowdfunding. Sharia fintech has a role in supporting the SGDS program on several objectives, especially related to the economy, such as decent work and economic growth, poverty reduction, hunger reduction, and the realization of prosperity.